(untitled) (Advances in Civil and Architectural Engineering, 2024)
The infrastructure of a country depends significantly on cement concrete as the primary construction material. The aggregate comprises a significant proportion of the overall volume of concrete. However, the ongoing extraction of granite rock to obtain coarse aggregate contributes to the escalating need for natural resources among future generations. Due to its high carbon dioxide (CO2) footprint, the cement industry is a significant contributor to global warming. An appropriate reduction in the amount of cement in concrete without affecting its key properties can result in economical and sustainable development of the construction industry. In this investigation, agricultural waste coconut shell is considered as a substitute for conventional aggregate in concrete to produce lightweight coconut shell concrete. The alccofine-1203 contains ultrafine particles with a distinctive composition that enhances the pozzolanic and hydration process in concrete. Alccofine ranging from 5 % to 15 % were added to cement. The results demonstrated that the 10 % alccofine enhanced the fresh and mechanical properties of the lightweight coconut shell concrete. Using a combination of coconut shell and alccofine in concrete would be the most environmentally sustainable option in the construction industry.